Educational Games for Soft-Skills Training in Digital Environments : New Perspectives /: New Perspectives. (2017) - Dell'Aquila, Elena; Marocco, ‎Davide; Ponticorvo, Michela; Di Ferdinando, Andrea; Schembri, Massimiliano; Miglino, Orazio
No abstract available